Optimization of lipid extraction from Tetraselmis sp. using different solvent systems at different ultrasonic extraction times - Calawigan, Roland Joseph C. (Miag-ao,Iloilo University of the Philippines in the Visayas, 2011)
This study was conducted to optimize lipid extraction from wet paste-like Tetraselmis sp. using different solvent systems namely : isopropanol : hexane, absolute ethanol and chloroform : methanol. Extraction were also done at different ultrasonic extraction times. Preliminary experiments were done to determine the best ratio for solvent mixtures. For isopropanol : hexane, the best solvent ratio is 90:10 and 1:1 ratio for chloroform : methanol. Prior to and after ultrasonic extraction, the samples were soaked in the solvent systems for ~ 18 hours and evaluated at different extraction times (0, 5, 10, 20 50 minutes). Statistical analysis showed that there is no interaction (P>0.05) between the ultrasonic extraction times and the solvent system. The best solvent system and ultrasonic extraction time is chloroform : methanol (1:1) at 50 minutes, respectively. Soaking effect was also evaluated and samples that were soaked method has a lower % crude lipid recovery (11.78%) than the ultrasonic extraction method (15.3%). Fatty acid analysis of the extracts from the different solvent systems showed no acid), C20:5n-3 (Eicosapentanoic acid).
Special Problem (M. of Chemistry) -- Miagao, Iloilo : University of the Philippines Visayas, October 2011.